Use Laplace transform to solve initial value problem.
Y^2+Y={t,0 less than or equal to t less than 1
{0,t greater or equal to 1
y(0)=0,y'(0)=0
Given Y'' + Y = "\\begin{cases}\nt, \\text{ if } 0 \\leq t < 1 \\\\\n0, \\text{ if } t \\geq 1\n\\end{cases}"
let f(t) = "\\begin{cases}\nt, \\text{ if } 0 \\leq t < 1 \\\\\n0, \\text{ if } t \\geq 1\n\\end{cases}"
we can express f(t) using unit step function U(t - a) = "\\begin{cases}\n0, \\text{ if } t < a \\\\\n1, \\text{ if } t \\geq a\n\\end{cases}"
hence we can express f(t) as f(t) = "t" "-" "t"U(t-1)
now given differential equation becomes, Y'' + Y = "t" "-" "t"U(t-1)
applying Laplace transform both side, ( "\\mathcal{L}"(f(t)) = F(s) )
"\\mathcal{L}"(Y'' + Y) = "\\mathcal{L}""(t" "-" "t"U(t-1))
"\\mathcal{L}"(Y'') + "\\mathcal{L}" (Y) = "\\mathcal{L}"( "t" ) "-" "\\mathcal{L}"("t"U(t-1))
s2Y(s) - sY(0) - Y'(0) + Y(s) = "\\frac{1}{s^2}" - e-s"\\mathcal{L}"(t+1)
s2Y(s) - sY(0) - Y'(0) + Y(s) = "\\frac{1}{s^2}" - e-s"\\frac{s+1}{s^2}"
since Y(0) = 0 and Y'(0) = 0 (as given)
s2Y(s) + Y(s) = "\\frac{1}{s^2}" - e-s"\\frac{s+1}{s^2}"
Y(s) = "\\frac{1}{s^2 (s^2+1)}" - e-s"\\frac{s+1}{s^2(s^2+1)}"
now applying the inverse Laplace transform we get,
"\\mathcal{L}^{-1}" Y(s) = "\\mathcal{L}^{-1}" ( "\\frac{1}{s^2 (s^2+1)}" - e-s"\\frac{s+1}{s^2(s^2+1)}" )
Y(t) = "\\mathcal{L}^{-1}" ( "\\frac{1}{s^2 (s^2+1)}") -"\\mathcal{L}^{-1}" (e-s"\\frac{s+1}{s^2(s^2+1)}" )
Y(t) = "\\mathcal{L}^{-1}" ( "\\frac{1}{s^2 } - \\frac{1}{(s^2+1)}") -"\\mathcal{L}^{-1}" (e-s"\\frac{s+1}{s^2(s^2+1)}" )
Y(t) = "\\mathcal{L}^{-1}" ( "\\frac{1}{s^2 } - \\frac{1}{(s^2+1)}") -"\\mathcal{L}^{-1}" (e-s"\\frac{s+1}{s^2(s^2+1)}" )
Y(t) = "\\mathcal{L}^{-1}" "(\\frac{1}{s^2 }) - \\mathcal{L}^{-1}(\\frac{1}{(s^2+1)})" "-\\mathcal{L}^{-1}" (e-s"\\frac{1}{s^2 (s^2+1)}"+ e-s "\\frac{s}{s^2 (s^2+1)}")
Y(t) = "\\mathcal{L}^{-1}" "(\\frac{1}{s^2 }) - \\mathcal{L}^{-1}(\\frac{1}{(s^2+1)})""+\\mathcal{L}^{-1}" e-s"(\\frac{1}{s^2 })" "-" "\\mathcal{L}^{-1}" e-s "(\\frac{1}{(s^2+1)})" +"\\mathcal{L}^{-1}" e-s"(\\frac{1}{s })" "-" "\\mathcal{L}^{-1}" e-s "(\\frac{s}{(s^2+1)})"
Y(t) = t - sin(t) + tU(t-1) -sin(t-1)U(t-1) - cos(t-1)U(t-1) +U(t-1)
Y(t) = t - sin(t) + (t -sin(t-1) - cos(t-1) +1)U(t-1) where U(t-1) is the unit step function.
Comments
Leave a comment